Oesophageal elongation with traction sutures (FOKER procedure) in a newborn baby with long-gap oesophageal atresia (LGEA): Maybe too early, maybe too dangerous? - Holger Till; Ina Sorge; Robin Wachowiak (Wolters Kluwer Medknow Publications, 2013)
In children with long gap oesophageal atresia (LGEA), the FOKER technique (oesophageal elongation with traction sutures) has been criticized for its high complication rate. We advocate analysing such problems to increase the safety in the future. The present case report will focus on timing. A female newborn (3000 g) with LGEA (gap of 5 cm) was delivered in an outward hospital. On day two of life, she received traction sutures on both pouches. By day five, all sutures had torn out, and a primary anastomosis was attempted. However, it leaked severely. Thus, on day ten, the oesophagus was approached from the neck converting the proximal end into a spit fistula and closing the distal end blindly. Furthermore, the gastro-oesophageal (GE-) junction was wrapped with a Teflon sling. When the baby arrived in our institution, she suffered from cavernous oesophageal masses extending from the thoracic inlet down to the diaphragm and fistulas draining them into the neck as well as into the right lung. Moreover, the Teflon sling had dislodged allowing for GE-reflux. In several stages, the oesophageal remnants were resected without any complications. Finally, Prof. Alaa Hamza performed a colonic interposition, which is working well today. In conclusion, the present case aims to caution paediatric surgeons to apply traction sutures for oesophageal elongation in newborns with LGEA.